2016
DOI: 10.1097/ico.0000000000000802
|View full text |Cite
|
Sign up to set email alerts
|

How Abnormal Is the Noncorneal Biometry of Keratoconic Eyes?

Abstract: Current analysis does not confirm the previously suggested association between keratoconus and higher amounts of axial myopia, which may have been the result of selection bias by using emmetropic eyes as a healthy control group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…18 In their study with KC patients, Rozema et al presented that the changes in VD and AL became significant when they removed ametropes from the control groups and left only the emmetropic eyes. 19 As in these studies that differentiate the control group from emmetropia, we measured AL as 24.94 ± 0.7 mm and 23.88 ± 0.96 mm, respectively, in the myopic group and KC group, and it was higher in favour of the myopic control group (p < 0.001). LT and VD were also higher in the myopic group.…”
Section: Discussionmentioning
confidence: 87%
“…18 In their study with KC patients, Rozema et al presented that the changes in VD and AL became significant when they removed ametropes from the control groups and left only the emmetropic eyes. 19 As in these studies that differentiate the control group from emmetropia, we measured AL as 24.94 ± 0.7 mm and 23.88 ± 0.96 mm, respectively, in the myopic group and KC group, and it was higher in favour of the myopic control group (p < 0.001). LT and VD were also higher in the myopic group.…”
Section: Discussionmentioning
confidence: 87%
“…Thin steep cornea and high, often extreme, asymmetric irregular astigmatism are inherent features of keratoconus; keratoconic eyes tend to have deeper anterior chamber depth measurements and higher spherical aberrations and HOAs, including coma and trefoil. 9,10,12,23 Abnormal corneal topography of both the anterior and posterior surfaces of the cornea showing higher than normal and irregular astigmatism and axial myopia and deep anterior chamber values impact IOL power calculation in keratoconic eyes. 1 Using conventional lens power calculation formulas often results in a hyperopic refractive outcome.…”
Section: Discussionmentioning
confidence: 99%
“…4,5,7,8 Different IOL calculation formulas perform well in average eyes; however, biometric values in eyes with keratoconus not only are characterized by extreme steep anterior keratometry readings with asymmetric irregular high astigmatism but also present with long axial length, steep posterior corneal power and curvature, thin central corneal thickness, and deep anterior chamber. [8][9][10][11][12] These measurements affect the estimated effective lens position (ELP) and may compromise the prediction of postoperative refraction in eyes with unusual ocular parameters. 4 Holladay and Kane have recommended specific modifications within their formulas for IOL power calculation in keratoconus.…”
mentioning
confidence: 99%
“…lens asphericity, that are difficult to obtain directly in a clinical setting. Given that it was recently demonstrated that keratoconic eyes only differ from normal eyes in their corneal shapes and anterior chamber depth, using lens parameters from a healthy eye model should not introduce any substantial errors. Once filled in, the model can be used to calculate the associated wavefronts, as well as the refraction in the form of spherical equivalent S.E., and Jackson power vectors J 0 and J 45 .…”
Section: Methodsmentioning
confidence: 99%